The significance of feeling safe for resilience of adolescents in sub-Saharan Africa - Bandeira, Monica; Graham, Marien A.; Ebersöhn, Liesel (Frontiers in Psychology, 2023)
Introduction Adolescents in sub-Saharan Africa (SSA) are exposed to several challenges and risk factors, linked to historical legacies. Sub-Saharan Africa has one of the highest rates of poverty and inequality in the world, is one of the regions most negatively affected by climate change, performs poorly on many health measures, and has high rates of different forms of violence, especially gender-based violence. These contextual challenges impact adolescent mental health outcomes, preventing them to access resilience-enabling pathways that support positive outcomes despite adversity. This study aimed to contribute to knowledge generation on resilience of young people in the understudied SSA region by investigating which variables directly (or indirectly) affect the resilience of adolescents. Methods Purposive sampling was used to collect quantitative survey data from 3,312 adolescents (females = 1,818; males = 1,494) between the ages of 12 and 20 years, participating in interventions implemented by a non-governmental organization, the Regional Psychosocial Support Initiative. Data were collected in Angola (385, 11.6%), Eswatini (128, 3.9%), Kenya (390, 11.8%), Lesotho (349, 10.5%), Mozambique (478, 14.4%), Namibia (296, 8.9%), South Africa (771, 23.3%), Uganda (201, 6.1%), and Zambia (314, 9.5%). The survey collected data on socio-demographic status, resilience (CYRM-R), depression (PHQ-9), self-esteem (Rosenberg Self-Esteem Scale) and feelings of safety (self-developed scale). Mental health was defined as lower levels of depression, higher levels of self-esteem and higher levels of feeling safe. A mediation analysis was conducted to investigate the relationship between the predictors (the socio-demographic variables) and the output (resilience), with the mediators being depression, self-esteem and feeling safe (which all link to mental health). Results This study contributes to a gap in knowledge on country-level comparative evidence on significant predictors that impact resilience outcomes (directly or indirectly) for adolescents in sub-Saharan African countries. The results indicate that, when considering all countries collectively, feeling safe is the only predictor that has a significant direct effect on overall resilience and personal resilience, but not on caregiver resilience. When considering each country separately, feeling safe has a direct effect on overall, personal and caregiver resilience for all countries; but not for South Africa and Mozambique. Discussion The results provide evidence on which to craft youth development interventions by measuring mediators (depression, self-esteem and feeling safe) and resilience for adolescents in sub-Saharan Africa. The overall results of the present paper point toward a contextually relevant pathway to supporting their resilience, namely, the need to systemically target the creation and/or strengthening of structures that enable adolescents to feel safe.